2015
DOI: 10.2174/1871520615666150518092547
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapeutic Impact of Toll-like Receptor Agonists in Breast Cancer

Abstract: Onset of tumors in breast cancer is a multi-factorial event at different ages and ethnic populations. The conventional treatment strategy suggests use of anti-estrogen drugs and selective estrogen receptor modulators (SERMs). Although, this strategy has achieved significant success to prevent tumor growth and metastasis and is still developing under an active field of research, the emergence of immunotherapy is a potential modern approach for breast cancer. In addition to SERMs, the screening of selective agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…All TLRs are type 1 transmembrane proteins and are localized in the cytoplasm, with the exception of TLR3, TLR7, TLR8, and TLR9, which are localized in the endosomal compartment. The strong expression of various TLRs by antigen‐presenting cells and their ability to induce antitumor mediators such as type I interferon triggered efforts to use TLR agonists in tumor therapy in order to stimulate the immune response toward antitumor responses …”
Section: Toll‐like Receptorsmentioning
confidence: 99%
“…All TLRs are type 1 transmembrane proteins and are localized in the cytoplasm, with the exception of TLR3, TLR7, TLR8, and TLR9, which are localized in the endosomal compartment. The strong expression of various TLRs by antigen‐presenting cells and their ability to induce antitumor mediators such as type I interferon triggered efforts to use TLR agonists in tumor therapy in order to stimulate the immune response toward antitumor responses …”
Section: Toll‐like Receptorsmentioning
confidence: 99%
“…TLR agonists are being evaluated in combination with immune checkpoint inhibitors (e.g., anti-PD-1, anti-PD-L1, anti-CTLA-4) for breast cancer treatment. TLR activation can prime the immune system and promote T cell activation, while checkpoint inhibitors alleviate the suppressive mechanisms that limit anti-tumor immunity ( 86 ). This synergistic approach aims to overcome resistance mechanisms and improve clinical responses in breast cancer patients ( 87 , 88 ).…”
Section: Targeting Toll-like Receptors For Improving Breast Cancer Im...mentioning
confidence: 99%
“…Compared to other counterparts, mushroom derived β-glucan had a highly branched main chain with a combination of glycosidic 1,3, 1,4, and 1,6 β-linkages [36,37]. Several studies reported that β-glucan obtained from G. lucidum was confirmed by 13 C NMR (Nuclear Magnetic Resonance) and FTIR (Fourier-transform infrared spectroscopy) spectroscopy with the most common chemical structure of β-glucan being β-1,3 backbone with different degrees of β-1,6 and/or β-1,4 branching [38,39].…”
Section: Identity Of the Interventionmentioning
confidence: 99%
“…As a matter of fact, the triggering of an immune response starts with the recognition of pathogen-associated molecular patterns, danger-associated molecular patterns, or both by a pattern recognition receptor (PRR) [6,7]. Moreover, a PRR agonist can serve as a vital component in activating specific (innate) and non-specific (adaptive) immune cells [8][9][10], which may become a prospective candidate to help managing an abberated immune response [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%